Antioxidant and anti-inflammatory activities of curcuma longa in an experimental study in rats with carrageenan-induced paw edema / Iylia Nur Diyana Ibrahim - Ibrahim, Iylia Nur Diyana (2009)
Turmeric, Curcuma longa L. (Zingiberaceae), has been attributed to a number of medicinal properties in the traditional system of medicine for treating several common ailments. I want to investigate the anti-inflammatory effect of Turmeric in rats with carrageenan-induced paw edema and alterations in the glutathione (GSH) level and the activities of antioxidative enzymes (superoxide dismutase, catalase, and glutathione reductase), as marker of acute inflammation, following oral administration of Turmeric and Acetyl Salicylic Acid (ASA) in rats with carrageenan-induced paw edema. In the previous studies, the researchers found that 1) Turmeric reduced the development of carrageenan-induced paw edema, to a greater degree than ASA; 2) Turmeric and ASA alleviated increases in the activities of catalase enzyme resulting from edema caused by carrageenan injection. These results suggest that the anti-inflammatory effect of Turmeric on carrageenan-induced acute inflammation can be attributed to its ameliorating effect on the oxidative damage.